Lama Simpan Herbisida Nabati Alang-Alang (Imperata cylindrica) dalam Menekan Pertumbuhan Gulma Bandotan (Ageratum conyzoides) - Marcella Noor Asysyifa Asysyifa; Lyswiana Aphrodyanti Aphrodyanti (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
The problem faced when using plant-based pesticides is that they are impractical, because plant-based pesticides must be made every time they are applied, so it takes more time. So far, vegetable herbicides have been made 1-3 days before application. It is not yet known exactly how long the shelf life of botanical herbicides is to suppress weeds. One of the vegetable herbicides that can be used is made from reed roots which can release allelopathic compounds. The ingredients found in the rhizomes of reeds (Imperata cylindrica) are known to contain allelopathic compounds in the form of saponins, tannins, arundoin, phenol, isoarborinol, cylindrin, simiarenol, campestrol, stigmasterol, β sitisterol, scopoletin, phydroxybenzalaldehyde, catechol, chlorogenic acid, oxalic acid, d-malic acid, citric acid, potassium, large amounts of calcium and 5-hydroxytryptamine. The aim of this research was to determine the effectiveness of the shelf life of the botanical herbicide Alang-alang roots on the growth of the weed A. conyzides. The design used in this research was a Completely Randomized Design (CRD) with 6 treatments and 4 replications and observations were carried out for 30 days. Making a botanical herbicide in the form of alang-alang root solution. The dose used is 150 ml. Data on the phytotoxicity of plant-based herbicides of Alang-alang roots were analyzed using analysis of variance with the F test and BNT further test at 5% level. The results of this study indicate that the shelf life of botanical herbicides affects the phytotoxicity of the weed A. conyzoides. All long storage treatments were considered to have an effective effect in suppressing bandotan weed (Ageratum conyzoides).